A companion to Eastern European cinemas - Imre, Anikó; Shaviro, Steven; Kinder, Marsha; Samardžija, Zoran; Ravetto-Biagioli; Portuges, Catherine; Bardan, Alice; Mazaj, Meta; Deshpande, Shekhar; Lovejoy, Alice; Sorenssen, Bjorn; Soldovieri, Stefan; et al. (Malden, MA : Wiley-Blackwell, 2012)
A Companion to Eastern European Cinemas showcases twenty-five essays written by established and emerging film scholars that trace the history of Eastern European cinemas and offer an up-to-date assessment of post-socialist film cultures.

Showcases critical historical work and up-to-date assessments of post-socialist film cultures
Features consideration of lesser known areas of study, such as Albanian and Baltic cinemas, popular genre films, cross-national distribution and aesthetics, animation and documentary
Places the cinemas of the region in a European and global context
Resists the Cold War classification of Eastern European cinemas as “other” art cinemas by reconnecting them with the main circulation of film studies
Includes discussion of such films as Taxidermia, El Perro Negro, 12:08 East of Bucharest Big Tõll, and Breakfast on the Grass and explores the work of directors including Tamás Almási, Walerian Borowczyk, Roman Polanski, Jerzy Skolimowski, Andrzej ¯u³awski, and Karel Vachek amongst many others
Introduction: Eastern European cinema from no end to the end (as we know it) / Anikó Imre -- New theoretical and critical frameworks. Body horror and post-socialist cinema: Gyorgy Polfis Taxidermia / Steven Shaviro -- El perro negro: transnational readings of database documentaries from Spain / Marsha Kinder -- Did somebody say Communism in the classroom? or, the value of analyzing totality in recent Serbian cinema / Zoran Samardzija -- Laughing into an abyss: cinema and Balkanization / Kriss Ravetto-Biagioli -- Jewish identities and generational perspectives / Catherine Portuges -- Aftereffects of 1989: Corneliu Porumboiu's 12:08 East of Bucharest (2006) and Romanian cinema / Alice Bardan -- Cinema beyond borders: Slovenian cinema in a world context / Meta Mazaj and Shekhar Deshpande -- Historical and spatial redefinitions. Center and periphery, or how Karel Vachek formed a new government / Alice Lovejoy -- The Polish black series documentary and the British Free Cinema movement / Bjorn Sorenssen -- Socialists in outer space: East German film's Venusian adventure / Stefan Soldovieri -- Red Shift: new Albanian cinema and its dialogue with the old / Bruce Williams -- National space, (trans)national cinema: Estonian film in the 1960s / Eva Näripea -- For the peace, for a new man, for a better world! Italian leftist culture and Czechoslovak cinema, 1945-1968 / Francesco Pitassio -- Aesthetic (re)visions. The impossible Polish new wave and its accursed Émigré auteurs: Borowczyk, Polanski, Skolimowski and Zulawski / Michael Goddard -- Documentary and industrial decline in Hungary: the "zd Series" of Tamás Almási / John Cunningham -- Investigating the past, envisioning the future: an exploration of post-1991 Latvian documentary / Maruta Z. Vitols -- East European historical epics: genre cinema and the visualization of a heroic national past / Nikolina Dobreva -- Nation, gender and history in Latvian genre cinema / Irina Novikova -- A comparative study: Rein Raamat's Big tõll and Priit Pärn's Luncheon on the grass / Andreas Trossek -- Yugoslav black wave: the history and poetics of polemical cinema in the 60s and 70s in Yugoslavia / Greg DeCuir, Jr. -- Industries and institutions. Follow the money: financing contemporary cinema in Romania / Ioana Uricaru -- An alternative model of film production: film units in Poland after WWII / Dorota Ostrowska -- The Hussite heritage film: a dream for all Czech seasons / Petra Hanukovu -- International coproductions as productions of heterotopias / Ewa Mazierska -- East is East? new Turkish cinema and Eastern Europe / Melis Behlil.
Bibliografije uz poglavlja. - Kazalo
Keywords: Motion pictures -- Europe, Eastern; Istočnoeuropski film